A Gender Bias in the Attribution of Creativity - Proudfoot, Devon; Kay, Aaron C.; Koval, Christy Z. (Psychological Science, 2015)
We propose that the propensity to think creatively tends to be associated with independence and self-direction—qualities generally ascribed to men—so that men are often perceived to be more creative than women. In two experiments, we found that “outside the box” creativity is more strongly associated with stereotypically masculine characteristics (e.g., daring and self-reliance) than with stereotypically feminine characteristics (e.g., cooperativeness and supportiveness; Study 1) and that a man is ascribed more creativity than a woman when they produce identical output (Study 2). Analyzing archival data, we found that men’s ideas are evaluated as more ingenious than women’s ideas (Study 3) and that female executives are stereotyped as less innovative than their male counterparts when evaluated by their supervisors (Study 4). Finally, we observed that stereotypically masculine behavior enhances a man’s perceived creativity, whereas identical behavior does not enhance a woman’s perceived creativity (Study 5). This boost in men’s perceived creativity is mediated by attributions of agency, not competence, and predicts perceptions of reward deservingness.